Analisis Kelas Kata Pada Tulisan Deskripsi Siswa Kelas VIII C SMP Muhammadiyah 6 Surakarta Tentang Karakter Teman Sebangku - Marmila, Prinata; , Drs. Yakub Nasucha, M.Hum (2015)
Learning Indonesian language and literature covers the four language skills, ie listening, speaking, reading, and writing. When compared with other language skills, writing skills is considered more difficult. In this study examined students' writing the description in which there is a class of words used by the students. In the course of writing a description of the students are groupings of words (word class) used by students in expressing his ideas. This study aims to (1) analyze the class of words contained in the text description of class VIII C SMP Muhammadiyah Surakarta 6 character friend bench and (2) analyzing the dominant class of words used class VIII C SMP Muhammadiyah Surakarta 6 character friend bench. The method used in this research is descriptive method. This study was a descriptive since the purpose of this study to describe or illustrate the analysis of speech in writing a description of the student. Methods for collecting data using the documentation techniques. Documentation techniques used to examine documents that analyze the class of words contained in the text deskrpsi students. While this research data analysis techniques using methods agih. Based on the analysis of data on writing a description class VIII C SMP Muhammadiyah Surakarta 6 character friend bench found the following results. Class words contained in the text description of the student is the noun word class (object), verb (work), adjektifa (nature), and the said task. Data generated every word class includes (1) the class of nouns (nouns) obtained 48 words, (2) class verb (verb) obtained 48 words, (3) the class or adjectives (adjectives) obtained 39 words, and (4 ) class assignments word obtained 17 words. While most dominant class of words used by students of class VIII C SMP Muhammadiyah Surakarta ie 6 classes of nouns (nouns). Class of nouns (nouns) that students use as many as 169 words covering 165 basic form nouns and noun form of derivative 31.